Split decisions: Family finance when a policy discontinuity allocates overseas work - Michael A. Clemens; Erwin R. Tiongson (Institute for the Study of Labor (IZA), 2012)
Labor markets are increasingly global. Overseas work can enrich households but also split them geographically, with ambiguous net effects on decisions about work, investment, and education. These net effects, and their mechanisms, are poorly understood. We study a policy discontinuity in the Philippines that resulted in quasi-random assignment of temporary, partial-household migration to high-wage jobs in Korea. This allows unusually reliable measurement of the reduced-form effect of these overseas jobs on migrant households. A purpose-built survey allows nonexperimental tests of different theoretical mechanisms for the reduced-form effect. We also explore how reliably the reduced-form effect could be measured with standard observational estimators. We find large effects on spending, borrowing, and human capital investment, but no effects on saving or entrepreneurship. Remittances appear to overwhelm household splitting as a causal mechanism.
Keywords: J61; O15; R23; 330; migration; households; remittances; policy discontinuity; Internationale Wanderung; Internationale Arbeitsmobilität; Familiensoziologie; Privater Haushalt; Rücküberweisung (Migranten); Philippinen; Migranten; Südkorea